Prevención de Caídas: Soluciones Para su Casa - Leigh Ann Martin (EDIS, 2006)
Revised! FCS2228-Span, a 1-page fact sheet by Leigh Ann Martin, is the Spanish language version of "Fall Prevention: Solutions for the Home," which lists home modifications that can be made to meet the needs created by the physical challenges of ageing. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, May 2006.